PEMASARAN TEMPURUNG KELAPA MENJADI ARANG YANG BERKUALITAS BERBASIS MEDIA SOSISL FACEBOOK PEKON AMBARAWA - Ahmad Sidkon Alwi; Sri Ipnuwati; Kasmi Kasmi; Wulandari Wulandari (LP3K Lampung, 2023)
Coconut shell is a solid waste from processed coconut which has been taken with coconut to get coconut milk. Coconut shells are generally used for fuel, household purposes or souvenirs. In Ambarawa village, Ambarawa sub-district is an area that produces coconut shell charcoal which is sold at low prices. To increase the economic value of society. The obstacle encountered in maximizing coconut shell waste is the lack of skills of the residents in exploiting the existing potential. This community empowerment program has the aim of having community welfare. This implementation is designed using a research method with a system of delivering material in theory or socialization and practice of the learning that has been done. Coconut shell charcoal can be used as an ingredient for coconut shell charcoal and activated carbon. The results of community service in Ambarawa village can have a positive impact in developing independent businesses to improve the welfare of the surrounding community